FAK in the nucleus prevents VSMC proliferation by promoting p27 and p21 expression via Skp2 degradation. Issue 4 (11th April 2021) - Jeong, Kyuho; Murphy, James M; Ahn, Eun-Young Erin; Lim, Ssang-Taek Steve
Abstract: Aims: Vascular smooth muscle cells (VSMCs) normally exhibit a very low proliferative rate. Vessel injury triggers VSMC proliferation, in part, through focal adhesion kinase (FAK) activation, which increases transcription of cyclin D1, a key activator for cell cycle-dependent kinases (CDKs). At the same time, we also observe that FAK regulates the expression of the CDK inhibitors (CDKIs) p27 and p21. However, the mechanism of how FAK controls CDKIs in cell cycle progression is not fully understood. Methods and results: We found that pharmacological and genetic FAK inhibition increased p27 and p21 by reducing stability of S-phase kinase-associated protein 2 (Skp2), which targets theCDKIs for degradation. FAK N-terminal domain interacts with Skp2 and an APC/C E3 ligase activator fizzy-related 1 (Fzr1) in the nucleus, which promote ubiquitination and degradation of both Skp2 and Fzr1. Notably, overexpression of cyclin D1 alone failed to promote proliferation of genetic FAK kinase-dead (KD) VSMCs, suggesting that the FAK-Skp2-CDKI signalling axis is distinct from the FAK-cyclin D1 pathway. However, overexpression of both cyclin D1 and Skp2 enabled proliferation of FAK-KD VSMCs, implicating that FAK ought to control both activating and inhibitory switches for CDKs. In vivo, wire injury activated FAK in the cytosol, which increased Skp2 and decreased p27 and p21 levels. Conclusion: Both pharmacological FAK and genetic FAK inhibition reduced Skp2 expression in VSMCs upon injury, which significantly reduced intimal hyperplasia through elevated expression of p27 and p21. This study revealed that nuclear FAK-Skp2-CDKI signalling negatively regulates CDK activity in VSMC proliferation. Graphical Abstract: